Peran Kamis Literasi dalam Penguatan Literasi dan Kemampuan Komunikasi Siswa SMPN 1 Masbagik - Zumratul; Hilmiyatun; Saufian Anhari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Indonesia's low reading interest, with only one in 1,000 people having a reading habit, has a direct impact on students' communication skills, since literacy and communication are inherently interconnected competencies that mutually reinforce one another. This study aims to describe the role of the Literacy Thursday program in strengthening literacy and communication skills of students at SMPN 1 Masbagik. The program has been running for years, held every Thursday morning on the school field with all school members participating. Students retell the content of books they have read at home on their own. Data collection was conducted in class 7.9 from March 12 to May 14, 2026, using a descriptive qualitative approach supported by quantitative data. Data were collected through observation, interviews, documentation, and speaking assessments using a rubric. Results show the average communication score increased from 58.9 to 78.4, with students meeting the passing standard rising from 25% to 84.4%. Students's willingness to speak in front of others also grew from 8 students (25%) to 27 students (84.4%). The program proved effective in building a reading culture and developing oral communication skills.